A resonant high-pressure sensor based on dual cavities. (9th November 2021) - Yu, Jie; Lu, Yulan; Chen, Deyong; Wang, Junbo; Chen, Jian; Xie, Bo
Abstract: High-pressure sensors enable expansive demands in ocean sciences, industrial controls, and oil explorations. Successful sensor realized in piezoresistive high-pressure sensors which suffer from the key issue of compromised accuracies due to serious temperature drifts. Herein, this paper presents a high accuracy resonant high-pressure sensor with the pressure range of 70 MPa. Different from conventional resonant high-pressure sensor, the developed sensor utilized a dual-resonator-cavity design to minimize temperature disturbances and improve the pressure sensitivities. Besides, four circle cavities were used to maintain a high vacuum level for resonators after anodic bonding process. In details, Dual resonators, which is parallelly placed in the tensile and compressive stresses areas of a rectangular pressure sensitive diaphragm, are separated vacuum-packaged in the parallel dual cavities. Thus, pressure under measurement bends the pressure sensitive diaphragm, producing an increased pressure sensitivity and a decreased temperature sensitivity by the differential outputs of the dual resonators. Parameterized mathematical models of the sensor were established and the parameters of the models were optimized to adjust the pressure sensitivities and the temperature sensitivities of the sensor. Simplified deep reactive ion etching was used to form the sensing structure of the sensor and only once anodic bonding was used to form vacuum packaging for the dual resonators. Experimental results confirmed that the Q values of the resonators were higher than 32 000. Besides, the temperature sensitivity of the sensor was reduced from 44 Hz °C −1 (494 ppm °C −1 ) to 1 Hz °C −1 (11 ppm °C −1 ) by the differential outputs of the dual resonators in the temperature range of −10 °C–60 °C under the pressure of 1000 kPa. In addition, the accuracy of the sensor was better than 0.02% FS within the pressure range of 110–6500 kPa and the temperature range of −10 °C–60 °C by using a polynomial algorithm.